2004
DOI: 10.1103/physreve.70.050301
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium two-phase coexistence in a confined granular layer

Abstract: We report the observation of the homogenous nucleation of crystals in a dense layer of steel spheres confined between two horizontal plates vibrated vertically. Above a critical vibration amplitude, two-layer crystals with square symmetry were found to coexist in steady state with a surrounding granular liquid. By analogy to equilibrium hard-sphere systems, the phase behavior may be explained through entropy maximization. However, dramatic nonequilibrium effects are present, including a significant difference … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
114
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(130 citation statements)
references
References 27 publications
13
114
3
Order By: Relevance
“…Nie et al (2000); Prevost et al (2004) reproduced certain features of cluster formation and two-phase co-existence by means of large-scale three-dimensional molecular dynamics simulations. Since realistic threedimensional simulations are still expensive and extremely time-consuming, simplified modelling of the effect of a vibrating wall by a certain multiplicative random forcing on individual particles was employed by Cafiero et al (1999).…”
Section: B Patterns In Driven Granular Gasesmentioning
confidence: 99%
See 4 more Smart Citations
“…Nie et al (2000); Prevost et al (2004) reproduced certain features of cluster formation and two-phase co-existence by means of large-scale three-dimensional molecular dynamics simulations. Since realistic threedimensional simulations are still expensive and extremely time-consuming, simplified modelling of the effect of a vibrating wall by a certain multiplicative random forcing on individual particles was employed by Cafiero et al (1999).…”
Section: B Patterns In Driven Granular Gasesmentioning
confidence: 99%
“…The experiments (Losert et al, 1999;Olafsen and Urbach, 1998;Prevost et al, 2004; demonstrated emergence and growth of multiple clusters but did not have sufficient aspect ratio to address the problem of coarsening in a quantitative way.…”
Section: Coarsening Of Clustersmentioning
confidence: 99%
See 3 more Smart Citations